Retinal detachments after Boston Keratoprosthesis: incidence, predisposing factors, and visual outcomes - Jardeleza, Maria Stephanie R. (Digit J Ophthalmol, 2015)
PURPOSE: To determine the rates, predisposing factors, and visual outcomes of retinal detachment (RD) after Boston Keratoprosthesis (KPro) implantation. METHODS: In this noncomparative, interventional case series, the medical records of 170 patients (205 eyes) who underwent Boston type 1 and type 2 KPro implantation at the Massachusetts Eye and Ear Infirmary between April 1993 and June 2009 were retrospectively reviewed. Incidence and annual rates of RD were calculated, and the roles of possible predictive factors for RD after KPro were investigated. Main outcome measures were rates of and risk factors for RD, visual acuity after RD, and surgical outcomes after repair. RESULTS: Sterile vitritis and autoimmune systemic disease significantly predisposed patients to RD after KPro placement. Of patients who developed RD after implantation, 50% progressed to visual acuity of no light perception despite surgical repair. CONCLUSIONS: Inflammation plays a major role in RD development after KPro implantation. Patients with predisposing factors should be advised of the high rates of RD and comanaged with a vitreoretinal specialist.